Ordinal cheap talk in common value auctions - Archishman Chakraborty; Nandini Gupta; Rick Harbaugh (Claremont McKenna College, Department of Economics, 2002)
Sellers benefit on average from revealing information about their goods to buyers, but the incentive to exaggerate undermines the credibility of seller statements. When multiple goods are being auctioned, we show that ordinal cheap talk, which reveals a complete or partial ordering of the different goods by value, can be credible. Ordinal statements are not susceptible to exaggeration because they simultaneously reveal favorable information about some goods and unfavorable information about other goods. Any informative ordering increases revenues in accordance with the linkage principle, and the complete ordering is asymptotically revenue-equivalent to full revelation as the number of goods becomes large. These results provide a new explanation in addition to bundling, versioning, and complementarities for how a seller benefits from the sale of multiple goods.
Keywords: D44; D82; L15; 330; linkage principle; winner's curse; cheap talk; Auktion; Informationsverhalten; Kommunikation; Theorie